Design and Numerical Study of the Novel Manifold Header for the Evacuated Tube Solar Collector - Martin Beer; Radim Rybár; Michal Cehlár; Sergey Zhironkin; Peter Sivák (Energies, 2020)
The presented paper dealt with the concept of an innovative manifold header for evacuated tube solar collectors. The proposed concept eliminates the drawbacks of conventional manifold headers, especially the serial connection of heat pipes that operate under uneven conditions. The advantage of the proposed design of the manifold header is also an increase in the heat exchange surface and the possibility of conducting the heat transfer media flow in a parallel flow arrangement, which increases the overall efficiency. The concept of the manifold header was evaluated on five variations of design with the use of the computational fluid dynamics (CFD) analysis. The results of the CFD analysis confirmed the functionality of the concept and also enabled the selection of the most suitable design elements, which were incorporated into the final design of a manifold header in the pre-prototype phase of manufacturing.